Optimasi Penggunaan Mutagen Kolkisin untuk Peningkatan Produktivitas Tanaman Stylo (Stylosanthes guianensis (Aubl.) Sw.): Optimalization of Colchicine Mutagen Utilization to Increase Stylo Productivity (Stylosanthes guianensis (Aubl.) Sw.) - Nindi Yulia; I Prihantoro; P D M H Karti (Jurnal Ilmu Nutrisi dan Teknologi Pakan (Nutrition and Feed Technology Journal), 2022)
Colchicine is a chemical that induced mutation in plants through doubling of plant chromosomes so that polyploid plants are produced which have a larger size than diploid plants. This study aimed to determine the optimal level and soaking time of colchicine to increase the productivity of stylo plants. This study used a Completely Randomized Factorial Design (CRD) with two factors and six replications. Factor A is a the colchicine level of 0 ppm, 25 ppm, 50 ppm, 75 ppm and 100 ppm. Factor B is the soaking time of 12 hours, 24 hours and 36 hours. The variables observed were vertical height, stem diameter, leaflets length, leaflets width and number of trifoliate leaves. The results showed that the colchicine at a level of 25 ppm with soaking time of 12 hours had a significant effect (p<0.05) on the increase in plant vertical height, stem diameter, and leaf width by 75.62 cm, 3.08 mm and 0.90 cm, respectively. The number of trifoliate leaves from the colchicine treatment and the length of the leaflets were not significantly different. The conclusion of this research is colchicine level of 25 ppm and soaking time of 12 hours can increase plant vertical height, stem diameter and leaf width on stylo plants aged 14 WAP (Weeks After Planting). Key words: colchicine level, productivity, soaking time, stylo